Qualidade e segurança alimentar: risco de contaminação por coliformes em alfaces produzidas e comercializadas em feira livre, de Uberlândia - MG - Mendonça, Larissa Silva (2014)
The consumption of fresh foods like fruits and vegetables without proper sanitization poses risks to human health, since such foods may be contaminated, being transmitters of various diseases. The water used for irrigation and washing these vegetables, as well as the transport vehicles and bunkers which are exposed to marketing represent possible sources of such contamination, compromising the quality of the product, and especially human health. The objective of this work was to study the contamination for total coliforms and Escherichia coli, in specific. In lettuce sold in an open market of Uberlândia-MG, analyzing the chain of production and marketing of lettuces and the microbiological quality of these sites in production in transport and marketing. Samples of irrigation and wash water and lettuces in each garden, and swab samples and lettuce were harvested in the means of transport and on newsstands. Was determined by colony forming unit (CFU / g or ml) of coliforms, fecal coliforms (E. coli), through the use of multiple tubes pretifilm technique (APHA, 2005). Was used for the water quality standard established by Resolution No. 357 of the National Environmental Council, CONAMA, and lettuces used the parameters of ANVISA, the DRC n0 12. Upon analysis of the samples was observed that will both irrigation water and wash as the means of transportation and banking are possible sources of microbiological contamination for total coliforms and in some cases even for fecal coliform as E.coli. Of total lettuce samples analyzed, 100% were within the standards established by the legislation, which is 10 ² CFU / g for both lettuce collected in production as those that were collected in transport and banking. Only lettuce 2 stalls showed the presence of E. coli, however these were among the limits allowed by law. In lettuce samples collected at the site of production and transportation is no presence of E. coli, which enables us to say that this contamination occurred in banking, during the process of marketing it were detected. Unlike other authors who have developed similar to that which presented significant research and / or high counts of fecal coliforms and E. coli, this research this requirement was considered satisfactory, and therefore analyzed the lettuces are fit for human consumption. Despite this finding the cleaning and sanitizing still leaking necessary since the total coliform count was significant in all analyzes. We can conclude from this work that although contamination by E. coli were not very significant and are within tolerable parameters, and in some cases present themselves absent, the risks of contamination exist throughout the chain of production, from planting to commercialization.